2014
DOI: 10.1093/molbev/msu271
|View full text |Cite
|
Sign up to set email alerts
|

Differential Effects of a Mutation on the Normal and Promiscuous Activities of Orthologs: Implications for Natural and Directed Evolution

Abstract: Neutral drift occurring over millions or billions of years results in substantial sequence divergence among enzymes that catalyze the same reaction. Although natural selection maintains the primary activity of orthologous enzymes, there is, by definition, no selective pressure to maintain physiologically irrelevant promiscuous activities. Thus, the levels and the evolvabilities of promiscuous activities may vary among orthologous enzymes. Consistent with this expectation, we have found that the levels of a pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
68
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(68 citation statements)
references
References 23 publications
0
68
0
Order By: Relevance
“…Compared with the other bifunctional enzymes, its kinetic parameters were relatively poor for both reactions (Table 1), yet it conferred substantial growth advantages on S. enterica cells grown in the absence of histidine, or in the absence of both histidine and tryptophan (SI Appendix, Table S1). Similarly complex relationships between enzyme activity and organismal fitness were observed when bifunctional variants of ProA were evolved to become responsible for steps in both proline and arginine biosynthesis (12). Perhaps significantly, HisA(dup13-15/D10G/G102A/G11D/G44E) had the highest measured K M for the HisA substrate, ProFAR (K M ProFAR = 100 μM; Table 1).…”
Section: Resultsmentioning
confidence: 84%
“…Compared with the other bifunctional enzymes, its kinetic parameters were relatively poor for both reactions (Table 1), yet it conferred substantial growth advantages on S. enterica cells grown in the absence of histidine, or in the absence of both histidine and tryptophan (SI Appendix, Table S1). Similarly complex relationships between enzyme activity and organismal fitness were observed when bifunctional variants of ProA were evolved to become responsible for steps in both proline and arginine biosynthesis (12). Perhaps significantly, HisA(dup13-15/D10G/G102A/G11D/G44E) had the highest measured K M for the HisA substrate, ProFAR (K M ProFAR = 100 μM; Table 1).…”
Section: Resultsmentioning
confidence: 84%
“…coli ProA (␥-glutamyl phosphate reductase), which catalyzes the second step in the pathway for synthesis of proline, has an inefficient promiscuous ability to catalyze the reduction of Nacetyl glutamyl phosphate (2,3). This reaction, normally catalyzed by ArgC, is essential for biosynthesis of arginine.…”
mentioning
confidence: 99%
“…However, a mutation that changes Glu383 to Ala in ProA allows the ⌬argC strain to grow, albeit slowly, on glucose (3). We previously found that E383A ProA (ProA*) has improved activity with the substrate for ArgC but substantially poorer activity with its normal substrate (2). (For technical reasons, both reactions were assayed in the reverse direction, but decreased activity in one direction implies decreased activity in the other, as well.)…”
mentioning
confidence: 99%
“…This fold improvement was not correlated with the original level of the promiscuous activity. Similarly, the decrease in the native activity varied from 190-to 2100-fold [38]. These results suggest that evolution of a novel enzyme may be possible with some orthologous enzymes, but not with all [39,40].…”
Section: Evolutionary Potential Of Promiscuous Functionmentioning
confidence: 83%
“…Thus, the levels and the evolvability of promiscuous activities may vary among these orthologous proteins. For example, there are nine gammaglutamyl phosphate reductase (ProA) orthologs, which display different level of promiscuity varying by about 50-fold [38]. A single amino acid change from glutamine to alanine near the active site seemed to be critical for enhanced promiscuous activity in these orthologous genes.…”
Section: Evolutionary Potential Of Promiscuous Functionmentioning
confidence: 99%